PERANCANGAN ABSENSI BERBASIS FACE RECOGNITION PADA DESA SOKARAJA LOR MENGGUNAKAN PLATFORM ANDROID - Darmansah Darmansah Darmansah; Ni Wayan Wardani; M Yoka Fathoni (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
The development of technology is currently very fast in various fields of human life. One of the uses of technology is in the field of attendance. Attendance is the most important part in an institution, both education, health, offices and government agencies in supporting monitoring of employees' daily attendance. Sokaraja Lor Village is a village located in Sokaraja District, Kab. Banyumas, Central Java. Currently the attendance process at the Sokaraja Lor village office is still using Pinjer Print and also using notes using a ledger. The use of this print pin is considered ineffective because if the village employee's hands are wet, or injured, attendance cannot be done and this is also a risk that village employees can leave absences to other employees. Seeing this, the researchers designed an attendance system based on Face Recognition using the Android platform. Face recognition-based attendance is attendance which is done using the detection of human face parts. Then in designing the face recognition-based attendance system, the researchers used a system modeling with Undifinied Modeling Language (UML). With the construction of this attendance system, Sokaraja Lor Village can make attendance easier in every condition because it is based on Android, then in recapitulating the list of employees who are present, the village government is easier because it has been stored in a database.